NPO FINANCIAL RESOURCE FORMATION MECHANISMS - A. V. Grishchenko (Финансы: теория и практика)
Viewed as the center of economic and social innovations, the «third sector» of the economy occupies a substantial niche in the current all-round development of the country.The need of reforming the financial relations of nonprofit organizations has been subject to a long-term discussion. The paper describes the principles of NPO finance organization, analyzes issues of the NPO development in the modern environment, NPO relationships with budgets of different levels as well as specifics of the government support of socially-oriented nonprofit organizations.The paper analyzes the legal basis for formation and replenishment of the NPO endowment, types of NPO activities allowing the endowment raising, requirements for nonprofit organizations as endowment owners. Along with that the principal areas of the endowment application are defined.